Uric Acid as a Potential Peripheral Biomarker for Disease Features in Huntington’s Patients - Corey-Bloom, Jody; Haque, Ameera; Aboufadel, Sameer; Snell, Chase; Fischer, Ryan S.; Granger, Steven W.; Granger, Douglas A.; Thomas, Elizabeth A. (Frontiers in Neuroscience, 2020)
Oxidative stress has long been implicated in the pathophysiology and progression of Huntington’s disease (HD). Uric acid (UA) is a naturally occurring antioxidant that is present in the brain and periphery. Growing evidence has implicated UA as a molecular biomarker for several neurodegenerative diseases, most notably Parkinson’s disease. In this study, we investigated UA levels in clinical samples from HD patients and normal controls and assessed potential relationships between UA levels and disease and clinical data. UA levels were measured in plasma (n=107) and saliva (n=178) samples from premanifest (pre-HD) and manifest HD patients and control subjects. Gender effects of UA levels were observed in both biofluids, with males showing higher UA levels compared to females. Comparisons of UA levels across diagnostic groups, separated by gender, revealed that both plasma and salivary UA levels were significantly lower in female pre-HD and manifest HD patients compared to normal controls. Salivary levels of UA were also significantly lower in male manifest HD patients vs. controls, but not in plasma. Correlations of peripheral UA levels to clinical data also showed differences according to gender. In male HD patients, both plasma and salivary UA levels were significantly negatively correlated with Total Functional Capacity (TFC), while positive correlations were observed with Total Motor Score (TMS). Female HD patients showed a significant positive correlation between plasma UA levels and TMS, while salivary UA levels from female patients were significantly correlated to disease burden. Finally, in a separate cohort, we show that UA levels are decreased in post-mortem prefrontal cortical samples (n=20) from HD subjects compared to matched controls. These findings suggest that decreased levels of UA in the brains of HD patients can be reflected in peripheral fluids, with salivary measures of UA particularly offering significant promise as a potentially relevant, non-invasive biomarker of disease symptoms and burden. Our findings further highlight the impact of sexual dimorphism in HD pathophysiology.